Sadd Dzariyah Review of Local Regulation Number 8 of 2007 Concerning The Prohibition of Buying from Hawkers and Giving Money to Beggars - Muhammad Iqbal Almuwafiqi; M. Junaidi (Proceeding International Conference Restructuring and Transforming Law, 2024)
The DKI Jakarta Regional Government has issued a regulation related to public order, namely article 40 point C of DKI Jakarta Regional Regulation Number 8 of 2007. The article states that it is prohibited for any person or business entity to become a beggar or instruct others to beg. In addition, article 40 on point c of the DKI Jakarta Regional Regulation also stipulates that it is prohibited for anyone or business entity to forbidden from hawkers and give a certain amount of money to beggars and the like, with the aim of reducing the number of beggars in DKI Jakarta. In this study the author formulates a problem, namely Sadd DzariyahAnalysis of the Prohibition of Giving Alms to Beggars in DKI Jakarta Regional Regulation Number 8 of 2007 This regulation is studied using the concept of Saddu Dzarî'ah which explains that an act that is initially permissible, if done will cause bad consequences (al-mafsadah).